Thank you will mark brainliest
![Thank you will mark brainliest class=](https://us-static.z-dn.net/files/d18/d1e185ffbe05d814ea78455847027796.png)
Answer:
Option D
Step-by-step explanation:
We have to find the value of the composite function (h o k)(2).
Since, (h o k)(x) = h[k(x)]
(h o k)(2) = h[k(2)]
From the picture attached,
At x = 2
k(2) = (-2)
Therefore, h[k(2)] = h(-2)
Since, h(x) = [tex]\frac{3}{x+1}[/tex]
Therefore, h(-2) = [tex]\frac{3}{-2+1}[/tex]
= -3
(h o k)(2) = -3 is the answer.
Option (D) is the correct option.